{Minimal access surgery in adolescent gynaecology} - Pandis, G.K.; Michala, L.; Creighton, S.M.; Cutner, A.S. (BJOG: An International Journal of Obstetrics and Gynaecology, 2009)
The benefits of a minimally invasive approach are now well documented in adult women, and thus surgeons have embraced the notion of expanding such expertise in adolescence with measured enthusiasm and a great sense of responsibility. Faster recovery is likely to have a positive impact on schooling, while less adhesion formation may reduce future fertility issues. Gynaecologists performing minimally invasive procedures in adolescents ought to be aware of the steep learning curve required for achieving proficiency with complex laparoscopic surgery. In the group of rare congenital anomalies and advanced endometriosis, the best surgical results can only be achieved after careful preoperative planning by a multidisciplinary team © 2008 The Authors.
Keywords: Adolescent gynaecology; Minimal access surgery